Association of Gross Motor Function Classification System Level and School Attendance with Bone Mineral Density in Patients With Cerebral Palsy - Jung, Ki Jin; Kwon, Soon Sun; Chung, Chin Youb; Lee, Kyoung Min; Sung, Ki Hyuk; Cho, Byung Chae; Chung, Myoung Ki; Moon, Seung Jun; Kim, Jaeyoung; Park, Moon Seok (Journal of Clinical Densitometry, 2018)
The present study aimed to evaluate bone mineral density (BMD) in children and adolescents with cerebral palsy (CP) and to critically analyze the effects of a variety of factors, particularly the Gross Motor Function Classification System (GMFCS) level, the Caregiver Priorities and Child Health Index of Life with Disabilities questionnaire, and the Pediatric Outcomes Data Collection Instrument (PODCI), on BMD. Fifty patients with CP who underwent dual-energy X-ray absorptiometry were included. Collected data included the extent of involvement, muscle tone, demographic data, factors determined through chart review, and laboratory results. Factors associated with BMD in this group were analyzed by performing multiple regression analysis. The mean Z-scores in male and female patients were −3.252 ± 1.822 and −3.789 ± 1.764, respectively, in the proximal part of the femur and −2.219 ± 1.323 and −2.451 ± 1.434, respectively, in the lumbar spine. In multiple regression analysis, the GMFCS level and the average frequency of missed school in the PODCI were significant factors associated with both femur and lumbar spine BMD. Both the GMFCS level and school attendance were independently associated with BMD and should be considered for the prevention and management of osteoporosis in patients with CP.
Keywords: Absenteeism; Absorptiometry, Photon; Adolescent; Bone Density; Cerebral Palsy; Child; Female; Femur; Humans; Lumbar Vertebrae; Male; Motor Skills; Schools; Bone mineral density; cerebral palsy; GMFCS; school attendance